Prevalence, risk factors and treatment outcomes of isoniazid resistant TB in Bulawayo city, Zimbabwe: A cohort study - Barbara Manyame-Murwira; Kudakwashe Collins Takarinda; Pruthu Thekkur; Bright Payera; Herbert Mutunzi; Raiva Simbi; Nicholas Siziba; Edwin Sibanda; Catherine Banana; Norbert Muleya; Evidence Makombe; Paula Littia Jongwe; et al. (Journal of Infection in Developing Countries)
Introduction: The isoniazid-resistant TB poses a threat to TB control efforts. Zimbabwe, one of the high TB burden countries, has not explored the burden of isoniazid resistant TB. Hence among all bacteriologically-confirmed TB patients diagnosed in Bulawayo City during March 2017 and December 2018, we aimed to assess the proportion with isoniazid resistant TB and associated factors. Also, we aimed to describe the TB treatment outcomes.